Metabarcoding Analysis of Pollen Species Foraged by Osmia excavata Alfken (Hymenoptera: Megachilidae) in China - Lu, Huanhuan; Dou, Feiyue; Hao, Youjin; Li, Yue; Zhang, Ke; Zhang, Huan; Zhou, Zeyang; Zhu, Chaodong; Huang, Dunyuan; Luo, Arong (Frontiers in Ecology and Evolution, 2021)
To meet the pollination need of economic crops, Osmia excavata has been successfully used to improve the pollination efficiency of Rosaceae and Brassicaceae plants. As a widely used pollinator of economic crops, a systematic study of flower-visiting species and diversities of O. excavata stocked in China was not found. To investigate the foraging pollen species and diversities of O. excavata, beebread from 20 experimental plots in China was collected by the trap-nesting method and analyzed by DNA metabarcoding technology. A total of 26 pollen plants in 14 genera and nine families were identified. A further analysis showed that the richness and abundance of the wild flowering plants in orchards and farmlands were lower than those in the nearby semi-natural habitats. The favorite pollen comes from economic crops apple and rape and wild flowering plants Juncus interior, Rosa gymnocarpa, and Rosa laevigata. Through a diversity index analysis, it was found that the Anhui region has the highest pollen plant diversity, while the Liaoning region has the lowest. Our results can provide a basis for flower-visiting species and diversities of O. excavata.